Global Challenges and ASEAN: Major Politico-Legal Issues Facing East Asia - Miyazaki, Takashi (UI Scholars Hub, 2012)
East Asia’s remarkable development and growth has had a considerable impact on the various aspects of international relations. In particular, ASEAN has played an important role in East Asia contributing to regional peace since its inception in 1967. Most East Asian nations have concentrated their national efforts on their economic development and popular welfare instead of engaging in armed conflict with their neighbor. ASEAN has thus achieved regional resilience and political influence in East Asia and beyond. Of this phenomenon, I will attempt in this article to highlight in specific terms the role ASEAN is internationally expected to play in the following four areas: 1) East Asian trade integration; 2) Prevention of global warming; 3) Trans-border movement of people including refugees; and 4) Conservation of traditional culture.